Ethno-Parenting in Islamic Education as a Model for Cultivating Children’s Moderate Attitudes - Amalia Hikmayanti Tambunan; Mhd Habibu Rahman; Nurhasanah Nurhasanah; Abdul Hakim (PT. Anagata Sembagi Education, 2026)
This article examines ethno-parenting in Islamic education as a contextual model for cultivating children’s moderate attitudes within Indonesian Muslim families. The background of the study arises from concerns about intolerance and rigid religious interpretations among youth, highlighting the need to strengthen moderation from the earliest educational environment, namely the family. Ethno-parenting is understood as a parenting pattern that integrates Qur’anic–prophetic values with local cultural wisdom that aligns with sharia. This study employs a qualitative library research design by analyzing accredited journal sources related to Islamic parenting, local cultural values, and religious moderation. Data were collected through systematic documentation and analyzed using thematic content analysis to identify intersections between Islamic educational principles and cultural practices in family life. The findings reveal that spiritual habituation, moral-social cultivation, and dialogic-democratic parenting methods embedded in local traditions create a lived environment where children internalize tolerance, empathy, balance, and non-violence. The discussion confirms that moderation is effectively formed through daily cultural-religious practices rather than doctrinal instruction alone. In conclusion, ethno-parenting offers a coherent framework that unites religion, culture, and parenting practice as the foundation for shaping moderate dispositions from early childhood in Indonesian Muslim families